Internet Plagiarism among Form Four Chemistry Students of a Selected Malaysian Secondary School: Exploring Its Prevalence, Correlates and Gender Differences - Hassan, Rajiah; Tunku Ahmad, Tunku Badariah (IIUM, 2017)
This case study was conducted to investigate the extent and prevalence of Internet plagiarism among a group of upper secondary students taking Chemistry as an elective subject at a selected public school in Kuala Lumpur. Eighty-seven (N=87) Form Four Chemistry students were required to write a two-page essay on acid rain as part of the School-Based Assessment exercise. The essays were examined in a quantified document analysis to record the occurrences and prevalence of plagiarism from Internet sources. Researcher-coded scores and Turnitin similarity indexes were used as the measures of Internet plagiarism. The results show that Internet plagiarism in this student body was widespread (99%) as almost everyone plagiarized, except one female student. The amount of information copied was extremely high at an average of 90% for Turnitin similarity indexes and 91.3% for researcher-coded scores. Gender wise, both boys and girls plagiarized at about the same extent, and the slight difference between them did not account for any statistical significance. Most were involved in high-scale plagiarism, and appeared to have lifted their essays completely off the Internet. However, the study could not completely ascertain whether students' lack of ability in English and Chemistry was the actual reason for their plagiarism act as measures of the two subjects turned out to be weak correlates of plagiarism. Based on the findings, the study recommends that students be explicitly taught the proper skills of writing and educated about the nature and implications of Internet plagiarism.